EU health stakeholders and patient safety (Italian Journal of Public Health, 2005)
The Standing Committee of European Doctors (CPME) has been actively promoting patient safety for a long time, well before the issue was given a firm place on the European and international agendas. Among its efforts to help raise the profile of patient safety, CPME organised a conference on the 4th and 5th April 2005 together with a group of EU health stakeholders that covered the whole spectrum of healthcare delivery.The European Conference ‘Patient Safety – Making it happen!’ took place in Luxembourg under the auspices of the Luxembourg EU presidency and EU Commissioner Kyprianou and resulted in the “Luxembourg Declaration on Patient Safety”.This Declaration contains recommendations to the EU, national authorities and healthcare organizations. It underlines the added value of the EU and recommends joining forces with the WHO Alliance for Patient Safety.A culture of transparency, trust and safety is being sought for through the suggested use of e-health, flows of health information, patient involvement and reporting systems. CPME saw perseverance and commitment pay off as patient safety is now seen as a priority by all health stakeholders and EU institutional bodies (European Commission, presidencies and Council). However all parties realise full well that the Luxembourg Declaration on Patient Safety is only the first step. All efforts are now focussed on follow up and implementation.
Keywords: Patient safety; Standing Committee of European Doctors; CPME and Luxembourg Declaration